Distribution, Biosynthesis, and Function of Carotenoids in Oxygenic Phototrophic Algae - Shinichi Takaichi (Marine Drugs)
For photosynthesis, oxygenic phototrophic organisms necessarily contain not only chlorophylls but also carotenoids. Various carotenoids have been identified in algae and taxonomic studies of algae have been conducted. In this review, the relationship between the distribution of chlorophylls and carotenoids and the phylogeny of sea and freshwater oxygenic phototrophs, including cyanobacteria, red algae, brown algae, and green algae, is summarized. These phototrophs contain division- or class-specific chlorophylls and carotenoids, such as fucoxanthin, peridinin, diadinoxanthin, and siphonaxanthin. The distribution of β-carotene and its derivatives, including β-carotene, zeaxanthin, violaxanthin, neoxanthin, diadinoxanthin, fucoxanthin, and peridinin (β-branch carotenoids), are limited to divisions of a part of Rhodophyta, Cryptophyta, Heterokontophyta, Haptophyta, and Dinophyta. Meanwhile, the distribution of α-carotene and its derivatives, such as lutein, loroxanthin, and siphonaxanthin (α-branch carotenoids), are limited to divisions of a part of Rhodophyta (macrophytic type), Cryptophyta, Euglenophyta, Chlorarachniophyta, and Chlorophyta. In addition, carotenogenesis pathways are also discussed based on the chemical structures of carotenoids and the known characteristics of carotenogenesis enzymes in other organisms. The specific genes and enzymes for carotenogenesis in algae are not yet known. Most carotenoids bind to membrane-bound pigment-protein complexes, such as reaction centers and light-harvesting complexes. Some carotenoids function in photosynthesis and are briefly summarized. Water-soluble peridinin-chlorophyll a-protein (PCP) and orange carotenoid protein (OCP) have also been characterized. This review is a summary and update from the previous review on the distribution of major carotenoids, primary carotenogenesis pathways, and the characteristics of carotenogenesis enzymes and genes.